2021
DOI: 10.1007/s13671-021-00329-2
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology Addressing Disparities in Health Care Access: a Review

Abstract: Purpose of Review Dermatologists have been at the forefront of researching telemedicine to expand access to care. The current COVID-19 pandemic has prompted even greater expansion and implementation of teledermatology. This review discusses the research examining the potential impact of teledermatology addressing disparities in care. Recent Findings Teledermatology appears to increase access to dermatology given expanded means to deliver care. Specifically, recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 81 publications
0
41
0
Order By: Relevance
“…Statistical data from NZ stats show the median age of the Waikato region to be 37.6 years in 2013 and 38.2 years in 2018 [ 33 ]. The convenience of the SSC referral method may encourage GPs to refer a greater proportion of older patients, as has been found in other studies [ 18 , 34 , 35 , 36 ]. A higher proportion of 2020 VLC referrals were from semi-rural locations compared to 2020 SSC pathway and 2016 VLC.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Statistical data from NZ stats show the median age of the Waikato region to be 37.6 years in 2013 and 38.2 years in 2018 [ 33 ]. The convenience of the SSC referral method may encourage GPs to refer a greater proportion of older patients, as has been found in other studies [ 18 , 34 , 35 , 36 ]. A higher proportion of 2020 VLC referrals were from semi-rural locations compared to 2020 SSC pathway and 2016 VLC.…”
Section: Discussionmentioning
confidence: 71%
“…The benefit of increased access to skin cancer screening by teledermoscopy, particularly in screening rural and low-income groups, has been well established [ 17 , 18 ]. A 2018 systematic review that included 16 studies, predominantly cross-sectional and observational, reported diagnostic accuracy in eight studies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…have been well described as positive interventions 15 ; in fact, even simple mobile phones have been shown to have great promise to help close gaps in access, but only if the gaps in phone ownership and access to these digital tools are closed. 16 The concern we explored in our survey-regarding the equity of telemedicine services-was identified early in the pandemic of 2020. Three main barriers to patients accessing care are commonly identified 17 : absence of technology (i.e., mobile phone or computer), digital literacy, and reliable internet coverage.…”
Section: Discussionmentioning
confidence: 99%
“…3 As a highly visual specialty, dermatology is particularly well-suited for telemedicine (ie, teledermatology). 4 This report details a patient case in which teledermatology was essential for identifying an atypical lesion as amelanotic melanoma. This case is a prime example of teledermatology's utility in expediting urgent dermatologic care, especially for rare skin cancers, the atypical appearances of which often result in missed diagnosis and worse prognosis.…”
Section: Introductionmentioning
confidence: 99%